All-nitrogen ion-based compounds as energetic oxidizers: a theoretical study on [N5+][NO3−], [N5+][N(NO2)2−], [NO2+][N5−] and NO2–N3. (23rd June 2020) - Sun, Qi; Wang, Pengcheng; Lin, Qiuhan; Lu, Ming
Abstract : The first four all-nitrogen pieces based energetic oxidizers, [N5 + ][NO3 − ], [N5 + ][N(NO2 )2 − ], [NO2 + ][N5 − ] and NO2 –N3 (N4 O2 ), were studied. Abstract : All-nitrogen ions, viz. N3 −, N5 +, and N5 −, are hot pieces to construct high-energy-density materials. However, all reported molecules containing these ions exhibit negative oxygen balance, which means that all those materials cannot serve as energetic oxidizers. Herein, we present optimized structures, thermochemical parameters and energetic properties of four new energetic oxidizers, viz. [N5 + ][NO3 − ], [N5 + ][N(NO2 )2 − ], [NO2 + ][N5 − ] and NO2 –N3, with very high oxygen balances (27.6–36.4%). Due to the presence of all-nitrogen-pieces, all these compounds exhibit extremely high heats of formation of 4.4–5.4 kJ g −1 (410.2–737.8 kJ mol −1 ), which cause these oxidizers to exhibit good detonation performance ( D : 7818–8873 m s −1 ; P : 25.6–35.6 GPa). It should be noted that all the oxygen balances, heats of formation, and detonation performances of all these energetic compounds were better than those of the state-of-the-art compounds, such as ammonium dinitramide (ADN). Among them, [NO2 + ][N5 − ] exhibited the best overall performance, thus making it to be a promising candidate as an energetic oxidizer.